Aprimoramento da gestão de riscos corporativos para o desenvolvimento de negócios de uma grande empresa nacional de alumínio - Nagashi, Bruna Colantonio (2021)
Subject: This work aims to present strategies for solving the problem faced by Aluminis on how to obtain, in a traditional company, the necessary attention to strategic issues related to the operationalization, participative management and culture of Corporate Risk Management for generation of shareholder value. Application: The analysis of the Company’s Corporate Risk management maturity, supported by interviews with the main managers of the Corporate Risk Management area and the special ized literature on this topic, revealed the need to review the main concerns regarding this issue, making it possible to start the intervention, with actions that reformulated the arrangement of points of attention in the process, in search of the desired evolution. Innovation: The diagnosis resulted in the direction of solutions for process innovations, considering mainly the sector in which the company operates, since it aggregates the development of the Corporate Risk Management methodology and its acculturation, including the risks related to the company strategy. Impact: This work is expected to help improve the company’s corporate risk management, by increasing its level of maturity, helping to mitigate the risks to which it is exposed, significantly increasing the participation of all employees and leadership in its daily management, as well as the synergy between the company’s strategic planning, the generation of shareholder value and a more mature Corporate Risk Management. Complexity: The main challenge faced in this work considers the engagement of all company employees, since it involves not only changes in processes and methodologies, but mainly in the company’s culture. The tone of leadership is of great importance for the success of the work, but without the active participation of all employees, corporate risk management becomes inefficient. Method and procedures: The methodology for solving problems and taking advantage of opportunities proposed by Marcondes, Miguel, Franklin and Perez (2017) was adopted. It started with the understanding of the problem, followed by its diagnosis, which led to the proposed solutions.